Effect of Fe-doping on the structure and magnetoelectric properties of (Ba0.85Ca0.15)(Ti0.9Zr0.1)O3 synthesized by a chemical route. Issue 5 (11th January 2016) - Venkata Ramana, E.; Figueiras, F.; Mahajan, A.; Tobaldi, David Maria; Costa, Benilde F. O.; Graça, M. P. F.; Valente, M. A.
Abstract : B-site Fe-doped (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 was synthesized by a facile chemical route to study the effect of doping on its physical properties. Abstract : B-site Fe-doped (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 was synthesized by a facile chemical route to study the effect of doping on its physical properties. Detailed analysis of X-ray diffraction and Raman spectroscopy data revealed an increased lattice strain and thereby deviation from the morphotropic phase boundary with the progressive doping of Fe from 1 to 5 mol%. Such structural changes have resulted in the weakening of the energy band gap as well as deterioration of the ferroelectric polar nature which was evidenced by a shift of tetragonal to cubic transitions towards room temperature and hard doping effects in ferroelectric hysteresis. The doped samples exhibited room temperature ferromagnetism. Combined Mossbauer and X-ray photoelectron spectroscopic studies suggest that oxygen vacancies and defect complexes induced by Fe doping play a major role in magnetic properties. Local piezoresponse measurements illustrated imprint characteristics of ferroelectric domains in undoped and doped samples at the nanoscale. Room temperature magnetoelectric (ME) measurements revealed that 1 mol% Fe doped sample, having higher ferroelectric polarization and moderate magnetization, exhibits a strong ME response with a coefficient of 12.8 mV cm −1 Oe −1 . The present study on Fe-doping effects on the structure and related ME properties of this important lead-free material is useful to tailor multiferroic applications in electronics.